Assessment of Denosumab in Korean Postmenopausal Women with Osteoporosis: Randomized, Double-Blind, Placebo-Controlled Trial with Open-Label Extension - Koh, Jung-Min; Chung, Dong Jin; Chung, Yoon-Sok; Kang, Moo-Il; Kim, In-Ju; Min, Yong-Ki; Oh, Han-Jin; Park, Il Hyung; Lee, Yil-Seob; Kravitz, Barbara; Waterhouse, Brian; Nino, Antonio; et al. (Yonsei medical journal, 2016)
The efficacy and safety of denosumab was compared with placebo in Korean postmenopausal women with osteoporosis in this phase III study. Women aged 60 to 90 years with a T-score of <-2.5 and ≥-4.0 at the lumbar spine or total hip were randomized to a single 60 mg subcutaneous dose of denosumab or placebo for the 6-month double-blind phase. Eligible subjects entered the 6-month open-label extension phase and received a single dose of denosumab 60 mg. Baseline demographics were similar in the 62 denosumab- and 64 placebo-treated subjects who completed the double-blind phase. Treatment favored denosumab over placebo for the primary endpoint {mean percent change from baseline in lumbar spine bone mineral density (BMD) at Month 6 [3.2% (95% confidence interval 2.1%, 4.4%; p<0.0001)]}; and secondary endpoints (mean percent change from baseline in lumbar spine BMD at Month 1, total hip, femoral neck, and trochanter BMD at Months 1 and 6, and median percent change from baseline in bone turnover markers at Months 1, 3, and 6). Endpoint improvements were sustained over 12 months in the open-label extension (n=119). There were no new or unexpected safety signals. Denosumab was well tolerated and effective in increasing BMD and decreasing bone turnover markers over a 12-month period in Korean postmenopausal women. The findings of this study demonstrate that denosumab has beneficial effects on the measures of osteoporosis in Korean postmenopausal women.